Threat appraisal and individual adaptation as drivers for collaborative drought management in the Netherlands - Lars De Graaff; Marthe L.K. Wens; Jaime Hoogesteger; Maurizio Mazzoleni; Anne F. Van Loon (Agricultural Water Management)
Drought risk is increasing worldwide. This is putting greater strain on agricultural production and the availability of freshwater resources. The agricultural sector needs to adapt to these increasing drought risks and must transition towards more sustainable and climate-robust production systems. This study aims to explore drivers, barriers, and opportunities for collaborative drought adaptation among farmers. An adapted version of the Protection Motivation Theory framework was developed and applied in a case study in the eastern Netherlands. To test this framework, we collected data using a mixed-methods approach; a combination of a survey, group discussions, and context interviews. We found that farmers with a high threat appraisal and experiences with drought adaptation measures were more likely to implement additional adaptation measures. Additionally, experiences with individual adaptation also increased farmers willingness to engage in collaborative drought management. Adaptation at landscape level was associated with a lower perceived cost and a higher perceived effectiveness, compared to individual adaptation. However, the lack of responsibility among the involved government agencies to initiate drought adaptation at the landscape level was a potential barrier for farmers to collaborate. Based on these results, we argue that lowering the financial risk for farmers through measures such as subsidies or compensation is essential. Additionally, increasing drought awareness among all involved stakeholders can create opportunities to move from intentions to actual collaborative adaptation behaviour.